Ethnomathematics: Numerical Literacy in the Dawan Language System Dialects of the Amanuban Tribe and its Relation to Mathematics Learning - Daniel, Farida; Suryadi, Didi; Prabawanto, Sufyani (KnE Social Sciences, 2024)
This research aims to describe the numerical literacy in the Dawan language system, the dialect of the Amanuban tribe, South Central Timor Regency in terms of ethnomathematics perspective and its relation to mathematics learning. This research is qualitative with an ethnographic research type. Data collection techniques were done through observation, interviews, and literature study. The results of this research indicate that the numerical literacy in the Dawan language system, the Amanuban dialect used by the community when using the number system is very unique. The uniqueness is that the community uses the base 10 number system with the unit base number 0 to 9 and the tens base number 10, which is used to calculate the next number using the concept of multiplication and addition. The mention of the name of the day in the Dawan language of the Amanuban dialect is also based on the unit base number system. This uniqueness can be used as a reference in learning mathematics with numbers, especially the concept of number sequences, the place value of a number, and addition and multiplication operations on integers for low-grade students who are fluent in Dawan. Keywords: dawan language system dialects of the amanuban tribe, ethnomathematics, mathematics learning, numerical literacy